Funding liquidity and bank lending - Dung Viet Tran (Cogent Economics & Finance, 2020)
We investigate how funding liquidity affects the bank lending using a large sample of US bank holding companies. We document a consistent evidence of a lower loan growth for banks that rely more on deposits. The quantile regressions which dissect the lending behavior of banks at the right tail of loan growth distribution point out the leveraged effect of funding liquidity is larger in high-loan-growth banks. The negative effects of funding liquidity on lending seem to be clearer before the crisis and especially for large banks. Interestingly, we do not find any evidence of the relation between lending and funding liquidity after the crisis period. We believe our study is of interest to regulators and policymakers.
Keywords: G21; G28; G34; G38; 330; bank lending; loan growth; funding; liquidity; deposits